Advances in biological and targeted therapies for systemic sclerosis. (3rd April 2023) - Mulcaire-Jones, Erica; Low, Andrea Hsiu Ling; Domsic, Robyn; Whitfield, Michael L; Khanna, Dinesh
ABSTRACT: Introduction: Systemic sclerosis (SSc) is a severe, and often life-threatening, autoimmune disease, which causes inflammation and fibrosis of the skin and internal organs. There are currently limited effective therapeutic options for patients with SSc. There are recently completed and ongoing phase 2 and 3 studies looking at biologic therapies for SSc that target the underlying pathogenesis of the disease. Areas covered: The purpose of this review is to describe completed and ongoing trials of different biologic therapies for the treatment of SSc. This review discusses biologic therapy directed at multiple pathways that are believed to contribute to inflammation and fibrosis in SSc including T cell, B cell, direct cytokines, and JAK signaling. Data presented is based on authors' expertise of completed and ongoing trials. Expert opinion: Tocilizumab and rituximab have supporting data to advocate for use in early SSc. Data from tocilizumab showed preservation of forced vital capacity (FVC) and beneficial effects on global composite measure. Recent data from different trials with rituximab in SSc (with and without interstitial lung disease) show beneficial effects on skin and FVC with good tolerability. We highlight the molecular heterogeneity in early SSc phenotype and the need to account for this in future trials.